Utilization of Simple Technology in Learning to Identify Vowel Letters for Second Grade Students with Mild Intellectual Disabilities at SLB Pelita Bunga, South Lampung - Andini, Mutiara; Sani, Yulvia; Utami, Ratna Tri (Universitas Sang Bumi Ruwa Jurai, 2025)
The research aims to examine the effectiveness of the use of interactive technology in helping children with intellectual disability recognize vowels. The research was conducted using the Classroom Action Research (CAR) method using a qualitative approach implemented in two cycles at SLB Pelita Bunga, South Lampung. The subjects in this study consisted of 5 children with mild intellectual disabilitiy in class II. Data collection techniques used observation, interviews, and documentation. The learning method used was learning by doing by inviting children to interact directly and practice what was in the application. The results of the study showed that the use of educational technology, especially the Marbel TK PAUD application, significantly improved children's ability to recognize vowels. In the first cycle, students showed increased involvement, but their letter recognition abilities were still limited. After the learning method was refined and the application was modified with more voice feedback and repetition features in the second cycle, students' abilities increased significantly. Interactive technology has been shown to improve the ability to recognize vowels. It is recommended that schools utilize similar technology as the main media in learning for children with special needs education.